Facets of Indian history - U.P. History Congress 2004 : Aligarh Muslim University); Sinha, A. K. (New Delhi : Anamika Publishers & Distributors, 2006)
Contributed papers presented at the 15th session of U.P. History Congress at Aligarh Muslim University on 2nd-3rd October, 2004.
Includes bibliographical references.
English and Hindi.
Keywords: India -- History -- Congresses